2006
DOI: 10.1007/s11745-006-5004-y
|View full text |Cite
|
Sign up to set email alerts
|

Solubility in and affinity for the bile salt micelle of plant sterols are important determinants of their intestinal absorption in rats

Abstract: Intestinal absorption of various plant sterols was investigated in thoracic duct-cannulated normal rats. Lymphatic recovery was the highest in campesterol, intermediate in brassicasterol and sitosterol, and the lowest in stigmasterol and sitostanol. Higher solubility in the bile salt micelle was observed in sitosterol, campesterol, and sitostanol than in brassicasterol and stigmasterol. The solubility of the latter two sterols was extremely low. When the affinity of plant sterols for the bile salt micelle was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 29 publications
6
46
0
Order By: Relevance
“…It has been found that the incorporation of sterols through Niemann-pick C1-like 1 protein (NPC1L1) 20) and simple diffusion 21) is an important determinant in their intestinal absorption. We must evaluate the possibility that NPC1L1 and simple diffusion might compensate for malfunction of ABCG5/ABCG8 in SHRSP rats.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the incorporation of sterols through Niemann-pick C1-like 1 protein (NPC1L1) 20) and simple diffusion 21) is an important determinant in their intestinal absorption. We must evaluate the possibility that NPC1L1 and simple diffusion might compensate for malfunction of ABCG5/ABCG8 in SHRSP rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also observed that the antimicrobial activity depends on the tested microorganisms and can cover the range from no antimicrobial activity up to very strong activity. One reason for this is the different lipid composition of the membrane of the microorganism [8,11,12,15], which strongly influences the membranolytic activity of detergents or peptides.…”
Section: Compartment Concentrationmentioning
confidence: 99%
“…mixed vesicles, mixed micelles, depending on the lipid to detergent ratio, are formed [8,9]. It is described that the microdomains contained in the mixed micelles were able to solubilise cholesterol [10][11][12][13][14]. An important aspect in the formation of mixed micelles lies in the fact that the mixed micelle association lowers the monomeric activity of bile salts and thus prevents the solubilisation and thus destruction and membranolytic effect of the apical membrane of the epithelial cells [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Solubility in bile salt micelles is thought to be an essential factor affecting the intestinal absorption of cholesterol and plant sterols 1 . Another important factor in the intestinal lumen is the releasability of monomer sterols from bile salt micelles before their incorporation into brush border membranes of intestinal epithelial cells 2,3 . The affinity of sterols for bile salt micelles determines their releasability from these micelles.…”
Section: Introductionmentioning
confidence: 99%
“…The 24 h lymphatic recovery of radiolabeled cholesterol was about 10-fold higher than that of radiolabeled sitosterol. Figure 3 shows the 24 h lymphatic recovery of various plant sterols and sitostanol 3 . The recovery of campesterol was highest, whilst those of stigmasterol and sitostanol were lowest, and those of brassicasterol and sitosterol were intermediate.…”
Section: Introductionmentioning
confidence: 99%